Development of Augmented Reality Based Comic Media Through Digital Library Applications for Visual Communication Capability - Masrukhin, Muhamad Johan; Fatih, Mohamad; Alfi, Cindya (FKIP-Universitas Riau, 2024)
Learning with more innovative media is needed to support students' abilities and also attract students' interest and attention. Apart from that, innovative media can also increase students' motivation and enthusiasm for learning. This research was conducted with the aim of developing augmented reality-based comic media to improve students' visual communication skills. This research was carried out using a 4D development model. The subjects of this research were class IV students at SDN Kendalrejo 01 Blitar Regency. The instruments used by researchers in conducting research are interviews, questionnaires, tests and also documentation. The data obtained by researchers was then analyzed to determine the level of feasibility and validity of the product. The media expert test results got a score of 97.5% and the material expert got a score of 95.8%. Researchers also conducted tests to see improvements in students' visual communication skills and obtained an average pre-test score of 70.75 and a post-test score of 95.5. The results of this research show that (1) Augmented reality-based comic media can improve students' visual communication skills. (2) The comic media developed by researchers is classified as very valid. This proves that comic media is effectively used in the learning process.